Study of Habitat Characteristic and Ethnobotanical Aspects of Komak Beans (Fabaceae) in North Lombok Regency - Yayat Maulidan; Sukiman Sukiman; Kurniasih Sukenti; Nur Indah Julisaniah; Rina Kurnianingsih (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Komak bean is one type of local beans that are quite widely cultivated. Komak beans have various important ingredients so that it can become alternative food stuffs and produce a variety of food products. North Lombok Regency is one of the komak bean cultivation center in West Nusa Tenggara. Information regarding the use and condition of the komak bean’s habitat in North Lombok Regency is not much known. Based on this, research is needed to be done related to the use and characteristics of komak bean habitats. This study aims to determine the diversity of komak bean, variety of utilization, habitat characteristics, and local wisdom in komak bean conservation. The methods used are field observations, interviews and measurements of environmental factors. Respondents were selected by purposive sampling and snowball sampling with semi-structured interview. In this study, the types of komak beans was found consisted of Lablab purpureus ssp. purpureus, Lablab purpureus var. lignosus, Lablab purpureus var. typicus, and Phaseolus lunatus. The variety of uses of komak beans in North Lombok Regency are as food ingredients, animal feed, a component of gifts in traditions, land barriers, and shade. Cultural Significance Index (CSI) value show P. lunatus as the most important type with value of 32 or almost used in all varieties of utilization. Komak beans grow at soil temperature ranges from 26℃-33℃, soil moisture 20-80%, 25℃-36℃ air temperature, air moisture 34-92%, and soil pH is range 4-8. The dominant texture of the soil are sandy clay and silty clay. Various traditional ways that are applied by the public to preserve komak seeds, namely mixing with rough salt, betel chalk and coconut oil, turmeric powder, and crushed seeds of Schleichera oleosa.